Fatores biopsicossociais que influenciam a prática de corrida em pessoas idosas - Biavatti, Stephanie dos Santos (2025)
Objective: This dissertation aimed to identify the main factors influencing participation and adherence to running practice among older adults. Methods: This is a mixed-methods, descriptive, exploratory-analytical, cross-sectional study with both quantitative and qualitative approaches. The research was conducted with 24 older adults who practice street running and reside in a municipality in northern Rio Grande do Sul, Brazil. In Scientific Production I, a cross-sectional, descriptive-correlational design was used. Data were collected through a questionnaire containing sociodemographic and clinical variables, as well as the Inventory of Motivation for Regular Physical and Sports Activity Practice (IMPRAFE-126). Statistical analysis was conducted using JASP software, with a significance level of α = 0.05. In Scientific Production II, semistructured interviews were conducted with open-ended questions about motivations, meanings, experiences, and perceptions related to running. The interviews were transcribed and analyzed using Bardin’s content analysis technique, supported by NVivo 10 software. The study complied with Resolution No. 466/2012 of the National Health Council and adhered to the General Data Protection Law (LGPD), Law No. 13.709/2018. Approved by the Research Ethics Committee under approval number 7.126.447. Results: Participants were predominantly male, white, married, with children, high educational level, and good perceived health, despite the presence of controlled chronic diseases. In Scientific Production I, perceived health was the main predictor of enjoyment in sports practice (F(1, 22) = 5.558; p = 0.028). In Scientific Production II, significant connections were identified between enjoyment, competitiveness, health, and sociability. Running was perceived as promoting physical and mental well-being, supporting active aging. Conclusion: The integration of quantitative and qualitative approaches allowed for a comprehensive understanding of the factors influencing participation and adherence to running among older adults. Perceived health, enjoyment, competitiveness, aesthetics, sociability, and stress control emerged as central elements in motivation and continued engagement in this activity. Street running stands out as an effective strategy for promoting holistic health and active aging in older populations.